ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DAN KEAKTIFAN BELAJAR SISWA SMP DI KABUPATEN BANDUNG BARAT - Nen Devi Eriani; Tia Audina; Gida Kadarisma; Wahyu Setiawan (Journal on Education, 2019)
This study aims to determine the level of mathematical communication skills and student learning activeness. The method used for analysis in this study is a Descriptive Qualitative Method that aims to be able to analyze the results of students' work on mathematical communication tests and search questionnaires on student learning activeness. The samples studied were 30 students from a total of 34 students of class IX-C at GUNUNGHALU 1 Public Middle School in West Bandung Regency in the 2018/2019 school year. The test questions used were mathematical communication as many as 3 questions as well as non-active learning instruments as many as 18 statements for each student. The results of the analysis obtained are mathematical communication skills and in junior high schools in West Bandung regency based on written description tests are still relatively low, especially on indicators linking diagrams into mathematical ideas, student learning activeness in learning mathematics is mostly not consistently involved in mathematics learning.